A luminescent single-molecule magnet of dimetallofullerene with cage-dependent properties. Issue 40 (3rd October 2019) - Nie, Mingzhe; Yang, Le; Zhao, Chong; Meng, Haibing; Feng, Lai; Jin, Peng; Wang, Chunru; Wang, Taishan
Abstract : A luminescent single-molecule magnet of dimetallofullerene exhibits cage-dependent properties. Abstract : It is important to explore luminescent single-molecule magnets (SMMs) to promote their application in high-density data storage. Herein, we report two dimetallofullerenes of DyEr@C82 isomers, which exhibit cage-dependent single-molecule magnet behavior and photoluminescence properties. DyEr@C82 isomers were characterized with a C s and C 3v cage symmetry by UV-vis-NIR spectroscopy and single-crystal X-ray diffraction analysis. Magnetic results revealed that DyEr@ C 3v -C82 displays SMM behavior below 3 K, whereas DyEr@ C s -C82 is a paramagnet. In addition, photoluminescence (PL) was also observed for both of these two isomers, whose peak patterns are different. Theoretical calculations revealed the presence of a one-electron-two-center Dy–Er bond in these two isomers, and different electronic structures of DyEr@ C s -C82 and DyEr@ C 3v -C82, which agrees well with the experimental results. These results show that dimetallofullerenes are promising magneto-luminescent materials with varied properties.